How general is general information construct? - Zarevski, Predrag (Array, 2005)
There is a small number of constructs in the field of differential psychology that have raised so much debate between psychologists and professionals in related disciplines as is the case with general (verbal) information construct. It seemed reasonable to test the validity of this construct measured with general information test in comparison with other measures of knowledge (cultural knowledge, vocabulary, knowledge of the most recent events), foreign language knowledge and standard verbal type g test. A sample of 376 candidates for state services was tested in a selection situation. Three analyses were conducted to determine the position of general information test in the space of other verbal competency measures. First analysis questioned latent structure of the space of 4 tests having the same format and questioning the knowledge of international terms, general culture, knowledge of most recent events, and general information. The second analysis included the g-factor intelligence test so to see how the above described structure changes when this new test is introduced. Third analysis introduced an English language test. In all of the three component analyses only one Eigenvalue was larger than 1 and it explained between 52-64% of the variance. In all analyses general information test had the highest projection on the only significant latent dimension of these cognitive spaces. In other words, it can be concluded that general information knowledge is in the center of this hyperconus. That is why we consider measurement of general information knowledge, as well as the construct itself, to be an important question in psychology. Thus, a summarized answer to the question in the title of this paper is: go further with the investigation of this construct because it does not seem that it is named “ general” information by chance.